Attention Deficit Hyperactivity Disorder : a Practical Guide for Teachers. - Cooper, Paul (Taylor and Francis, 2013)
This is a clear and concise guide to classroom practice for teachers dealing with pupils with attention deficit / hyperactivity disorder, a condition that is estimated to affect on average one in every twenty-five children. In this new and revised edition, the authors present in an accessible style and with regard for the everyday realities of the classroom life: key issues commonly raised by teachers about AD/HD; sources of information on the nature and assessment of AD/HD; advice to teachers on how to communicate with both parents and professionals; and practical classroom strategies and int.